Pembuatan Lilin Aromaterapi Anti Stress dan Repellent sebagai Peluang Usaha di Dusun Mon Singet, Desa Kajhu, Aceh Besar - Meilina, Hesti; Sri Mulyati; Suparno; Yunardi; Mukramah; Aula Chairunnisak; Wahyu Rinaldi; Khansa Syarahil Putri (Akademi Farmasi YPPM Mandiri, 2023)
Aromatherapy candles are one of the best-selling and popular products. Apart from being used as therapy by means of inhalers, it is also widely used as wedding souvenirs and souvenirs from certain areas by highlighting the distinctive aroma of that area. The Community Service Team chose an aromatherapy candle product as a product that has good business opportunities for mothers and young women in Mon Singet Hamlet, Kajhu Village, Aceh Besar District. Essential oils or essential oils used in making aromatherapy candles are lime and lemongrass, each of which has effectiveness for relaxation (anti-stress) and as a repellent or mosquito repellant. The results of the training show the enthusiasm of the participants in making aromatherapy candles with various attractive shapes and colors. In addition, the participants also understood the ingredients for making aromatherapy candles, their benefits and potential to be used as business opportunities.